Meningkatkan Minat dan Hasil Belajar IPA melalui Pembelajaran Kooperatif Tipe Group Investigation (GI) di Kelas IX IPA SMP Negeri 4 Tapung Hulu - Asniah, Asniah; Apriani, Jeli; Afriyanis, Afriyanis; Rodhiya, Rodhiya (Tematik: Jurnal Penelitian Pendidikan Dasar, 2023)
The study aimed to assess the effectiveness of GI learning in enhancing science learning outcomes for ninth-grade students at SMP Negeri 4 Tapung Hulu. Conducted through Classroom Action Research (PTK) in two cycles, the research involved stages of action planning, implementation, observation, and reflection. Participants included 35 ninth-grade students during the 2019/2020 academic year, with collaborative efforts from science teachers. Data collection involved observation, evaluation, documentation, and interviews. Findings indicate that GI learning positively impacts science learning outcomes, as evidenced by increased student engagement and achievement. In the first cycle, 25.6% of students showed improved competencies in living things classification, with 74.4% achieving completeness. The second cycle saw further improvements, with only 12.8% not reaching completeness and 87.2% exceeding 75% completeness. Student discussion activities notably increased, attributed to positive responses towards tasks. It is recommended for teachers to foster a culture of curiosity and creativity to enhance learning experiences. The author welcomes feedback to enhance the report's quality, acknowledging potential areas for improvement.